PENERAPAN MODEL PEMBELAJARAN RME TERHADAP PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH SISWA SMKN 1 SEMEN - Siti Retnosari; Bambang Agus Sulistyono; Samijo (Afore : Jurnal Pendidikan Matematika, 2026)
Based on the observation results, it was found that students still have difficulty in solving problems, especially in story problems that require contextual reasoning, the methods used by teachers have not been able to fully encourage students to think critically. The purpose of this study is to apply the RME model to improve students' mathematical problem-solving abilities. This study uses a quantitative approach with an experimental method. This study was conducted at SMK Negeri 1 Semen, with a sample taken of class X AKL 1 totaling 32 students in the 2025/2026 academic year. Data were analyzed using the Paired Sample T-Test. The results of the analysis show an increase in students' mathematical problem-solving abilities by applying the RME learning model, especially in story problems on exponential function material. In this case, students are actively involved in group discussions to identify the problems given. Teachers also play an optimal role in each stage of learning the RME model. Thus, the application of the RME model is quite effective and provides positive results for mathematics learning.